The Record of the Perpetrators of Misdemeanors - Milić, Ivan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
A focus of the author’s attention in this article is the Register of Penalties of misdemeanor perpetrators which figures as a novelty in the Misdemeanor Law. In the introduction, the records of the perpetrators of criminal acts, economic offenses and misdemeanors will be generally discussed. Thereupon, the Law stipulations on the entry, deletion, and providing of the data contained in the Register of Penalties will be presented. The main aim of the article is reflected in the author’s endeavors to show that the legislator did not pay much attention to the regulation of the Register keeping, which consequently will cause substantial problems in practice giving that the Law is to some extent contradictory and incomplete. The author, furthermore, seeks to detect the ratio of the introduction of the Register of Penalties and the consequences to be borne by a person inscribed in this Register.